2021
DOI: 10.3389/fonc.2021.706883
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of SLC16A1 as a Biomarker to Predict Poor Prognosis of Urological Cancers

Abstract: ObjectiveTumor metabolism has always been the focus of cancer research. SLC16A1, as a key factor in catalysis of monocarboxylate transport across the plasma membrane, has been found to be associated with the occurrence and metastasis of a variety of cancers, but its prognostic significance and mechanism in different tumors are still unclear.MethodsBased on the gene expression matrix and clinical information of human cancer tissues acquired from TCGA and GTEX databases, the differential expression of SLC16A1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…29 Additional candidates are reported to be involved in cancer prognosis and progression, including TSPAN11, 30 NKX6-1, 31 and SLC16A1. 32 Gene enrichment analysis 33 identified significant associations (adjusted p < 0.05) between our gene candidates and macular thickness and degeneration, as seen in previous human GWAS studies 34 and cataract formation (Elsevier pathway collection), 35 as well as non-eye related diseases such as bone mineralization, tumor suppression, and Amyloid Precursor Protein pathways (Biocarta). 36 Gene Ontology (GO) term analysis of our gene candidates revealed significant enrichment (adjusted p < 0.05) for protein tyrosine kinase activator activity, gap junction channel activity, and wide pore channel activity (Figure 4B).…”
Section: Gwas and Experimental Validation Of Alksupporting
confidence: 65%
See 1 more Smart Citation
“…29 Additional candidates are reported to be involved in cancer prognosis and progression, including TSPAN11, 30 NKX6-1, 31 and SLC16A1. 32 Gene enrichment analysis 33 identified significant associations (adjusted p < 0.05) between our gene candidates and macular thickness and degeneration, as seen in previous human GWAS studies 34 and cataract formation (Elsevier pathway collection), 35 as well as non-eye related diseases such as bone mineralization, tumor suppression, and Amyloid Precursor Protein pathways (Biocarta). 36 Gene Ontology (GO) term analysis of our gene candidates revealed significant enrichment (adjusted p < 0.05) for protein tyrosine kinase activator activity, gap junction channel activity, and wide pore channel activity (Figure 4B).…”
Section: Gwas and Experimental Validation Of Alksupporting
confidence: 65%
“…29 Additional candidates are reported to be involved in cancer prognosis and progression, including TSPAN11 , 30 NKX6-1 , 31 and SLC16A1 . 32…”
Section: Resultsmentioning
confidence: 99%
“…MEF2C has reported roles in numerous age-related conditions, including Alzheimer’s disease ( Xue et al, 2021 ) and muscle wasting in cancer ( Judge et al, 2020 ) and GRM is associated with age-related hearing loss ( Liu et al, 2021b ). Additional candidates are reported to be involved in cancer prognosis and progression, including TSPAN11 ( Liu et al, 2021a ), NKX6-1 ( Su et al, 2021 ), and SLC16A1 ( Zhang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study and for the first time, hsa_circ_0013561 (circ-SLC16A1) was investigated in tissues from patients with NSCLC, and circ-SLC16A1 expression levels were demonstrated to be significantly upregulated in NSCLC tissues and cell lines. Previous studies have confirmed that SLC16A1 is expressed in almost all human tissues and overexpressed in many cancers, indicating poor prognosis [ 13 – 15 ]. Also, circ-SLC16A1 was mainly located in the cytoplasm, similar to other circRNAs [ 16 ].…”
Section: Discussionmentioning
confidence: 99%